Numerical investigation on combustion characteristics of premixed hydrogen/air in a swirl micro combustor with twisted vanes. (18th November 2021) - Gao, Wei; Yan, Yunfei; Huang, Lujing; Zhang, Weiwei; Shen, Kaiming
Abstract: The combustion characteristics of the swirl micro combustor with twisted vanes (Swirl-MC-TV) and the conventional micro combustor (Conventional-MC) are investigated and compared under different inlet velocities (8–40 m/s), wall materials (quartz, steel, and SiC), and equivalence ratios (0.6–1.4). The results show that the larger area of recirculation zones and the stronger recirculation intensity are the key factors for Swirl-MC-TV to stable combustion. When the inlet velocity is 40 m/s, compared with the Conventional-MC, the wall heat loss of the Swirl-MC-TV is reduced by 15.9%, and the reaction heat and combustion efficiency of the Swirl-MC-TV are increased by 17.5% and 5.9%, respectively. When the wall materials of steel and SiC, combustors have a better preheating effect and higher combustion intensity. When the equivalence ratio is greater than 0.6, the wall heat loss of Swirl-MC-TV is larger but the combustion efficiency and the reaction intensity are still higher than Conventional-MC. Graphical abstract: Image 1 Highlights: The Swirl-MC-TV has larger recirculation zone and stronger recirculation intensity. The flame in Swirl-MC-TV is fixed in the outlet area of the swirler. The Swirl-MC-TV has smaller wall heat loss and higher combustion efficiency. The combustors with steel and SiC as wall materials have better preheating effects.